2016
DOI: 10.1007/s00253-016-8010-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of humic acid on anaerobic digestion of cellulose and xylan in completely stirred tank reactors: inhibitory effect, mitigation of the inhibition and the dynamics of the microbial communities.

Abstract: Inhibition effect of humic acid (HA) on anaerobic digestion of cellulose and xylan and the mitigation potential of the inhibition were evaluated in controlled fed batch reactors at 30°C and a hydraulic retention time (HRT) of 20 days. Reactor performances were evaluated by biogas production and metabolite measurements for 220 days. Microbial population dynamics of the reactors were monitored with nextgeneration 16S rRNA gene sequencing at nine different sampling times. Our results showed that increasing levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(31 citation statements)
references
References 67 publications
0
29
0
Order By: Relevance
“…In another investigation, in the process of anaerobic cellulose and xylan digestion with crushed anaerobic granular sludge that was realized with the introduction of HCs (Sigma-Aldrich; CAS number 68131-04-4) at concentrations of up to 0.4 g/L, microbiological analysis showed that the concentrations of bacterial cells of the genera Clostridiales, Bacteroidales, and Anaerolineales, as well as hydrogenotrophic methanogens, were significantly reduced in the presence of HCs [29]. It was found that the relative number of bacteria of Methanobacteriaceae and Methanomicrobiales-WCHA208 was greatly reduced in the presence of HCs, whereas the number of Methanosaetacea bacteria did not change.…”
Section: Discussionmentioning
confidence: 99%
“…In another investigation, in the process of anaerobic cellulose and xylan digestion with crushed anaerobic granular sludge that was realized with the introduction of HCs (Sigma-Aldrich; CAS number 68131-04-4) at concentrations of up to 0.4 g/L, microbiological analysis showed that the concentrations of bacterial cells of the genera Clostridiales, Bacteroidales, and Anaerolineales, as well as hydrogenotrophic methanogens, were significantly reduced in the presence of HCs [29]. It was found that the relative number of bacteria of Methanobacteriaceae and Methanomicrobiales-WCHA208 was greatly reduced in the presence of HCs, whereas the number of Methanosaetacea bacteria did not change.…”
Section: Discussionmentioning
confidence: 99%
“…Y.M. Amha et al Bioresource Technology 247 (2018) decrease in relative abundance of hydrolytic/fermentative bacterial populations including Clostridiales, Bacteroidales, and Anaerolineales (Azman et al, 2017). Inhibition due to LCFA has also been reported, with inhibition of hydrolytic bacteria occurring at 2.6-9.4 kg COD m −3 and acidogenic bacteria at a similar concentration range, 2.1-7.9 kg COD m −3 .…”
Section: Pcr-dggementioning
confidence: 99%
“…Hydrolytic bacteria are inhibited by elevated levels of VFAs, LCFAs, hydrogen partial pressure, and humic acids (Azman et al, 2017;Azman et al, 2015;Cazier et al, 2015) (Tables 1-4). Inhibition occurs via activity loss, reversible reduction of hydrolases (e.g., when inhibitors bind to enzyme active sites or substrate-enzyme complexes), or irreversible impacts resulting from changes in enzyme chemical structure (Azman et al, 2015).…”
Section: Hydrolysis and Fermentationmentioning
confidence: 99%
“…However, there are examples where Methanothrix seems to be more resistant. Methanothrix is more resistant to longchain fatty acids (Silva et al 2016) and humic substances (Azman et al 2017) than Methanosarcina. The higher tolerance in these cases was thought to be related to the different cell wall structure.…”
Section: Physiological Propertiesmentioning
confidence: 99%